Fatigue Assessment of Floating Offshore Wind Turbine Tower under Wind-Wave Coupled Loading - Zhang, Jiaxin; Heng, Junlin; Dong, You; ICASP14 (My University, 2023)
Floating offshore wind turbine towers (FOWTs) shows promising possibilities in the exploitation of the affluent Aeolian source at the deep ocean. However, the taller FOWT is also highly prone to fatigue damage under the combination of wind-wave-servo loads, especially in the high-strength bolt of the ring flange connection between tower shells. This study carries out an in-depth fatigue life of bolts in tower flanges using the site-specific data, in which the reference turbine DTU 10MW is considered with both the floating and fixed-bottom foundations. Firstly, based on the in-situ wind data in Mexico Gulf, the wind-wave loading features are determined, including the wind speed, direction and correlation between the wave height and wind speed. Then, by employing the multi-physics simulation tool OpenFAST, the wind and wave data are transferred into random excitations as input to the numerical model. Accordingly, the load history is derived for the tower shell near the flange of interest, followed by a further transition into bolt forces via the load transfer function (LTF). Finally, for both the floating and fixed-bottom towers, the time-variant fatigue damage is estimated based on the bolt force and probability-stress-life (P-S-N) curve, while the fatigue life is predicted accordingly. Especially, the influence of floating foundations on the fatigue life of bolts is discussed through comparisons. In general, this study not only offers a constructive reference for the further application of FOWTs, but also highlights the urgent demands to improve the fatigue endurance of bolts by joint efforts from both the design, fabrication and maintenance.
14th International Conference on Applications of Statistics and Probability in Civil Engineering(ICASP14)
PUBLISHED